Property Rights Conservation and Development: An Analysis of Extractive Reserves in the Brazilian Amazon - Danilo Camargo Igliori; Timo Goesch (Fondazione Eni Enrico Mattei (FEEM), 2004)
The economic literature of property rights has been assessing the impact of different community based arrangements on the efficiency of natural resource management of specific areas. Differently, other strands of development economics and policy-oriented research have been concerned with issues such as poverty alleviation, technological progress and the capability to compete in market economies, which go beyond the local areas where traditional communities live and include the wider economy. The extractive reserves in the Brazilian Amazon offer perhaps one of the most interesting cases for investigating the connections between these two approaches in the context of tropical forests. It is based on the idea that the combination of public property with collective use in particular forest areas can generate competitive and, at the same time, sustainable exploitation of its natural resources. This paper aims to analyse whether the existing property rights support the joint objective of conservation and development. Our main result is that current property rights systems are efficient only with respect to competition in markets for existing extractive products. This finding points out to a fundamental contradiction between the static structure of the property rights systems and the dynamic nature of two most promising development paths, namely the discovery of new products and the supply of biological inputs for plantations. The current model of extractive reserves based on the design of internal property rights fails to taken into account the broader economic context where the reserves must generate a viable revenue stream. We conclude therefore that under the current set of institutions, the development objectives inherent in the extractive reserves model are likely to face probably considerable challenges to be accomplished in the future.
Keywords: O13; Q23; 330; Property rights; Extractive reserves; Environment and Development; Sachenrecht; Artenvielfalt; Rohstoff; Amazonasgebiet; Brasilien